Teaching the History of Christianity: Critical Themes and Challenges - Killen, Patricia O'Connell (Teaching theology and religion, 2009)
At the November 2008 meeting of the American Academy of Religion, the History of Christianity section sponsored a panel around the question: “What are the key challenges, opportunities, and goals in the History of Christianity classroom today and how best should teachers respond to them?” Beginning with brief sketches of institutional context and identification of one or more pivotal choices each makes in the course they teach, the panelists explored critical themes and issues that arise in teaching the history of Christianity, first with each other and then through interchange with the audience.